Odpowiedzi

  • Użytkownik Zadane
2009-05-21T17:54:58+02:00
(3+x²)²= 9 + 6x² + x⁴
(5a-2b)²= 25a²- 20ab + 4b²
(-5+x)²= 25 -10x + x²
(-6y-3)²= 36y² + 36y + 9
(-3x+1)(1+3x) = 1 - 9x²
2009-05-21T17:55:01+02:00
(3+x²)²=9+6x²+x⁴
(5a-2b)²=25a²-20ab+4b²
(-5+x)²=25-10x+x²
(-6y-3)²=36y²+36y+9
(-3x+1)(1+3x)=-3x-9x²+1+3x=-9x²+1
2009-05-21T17:57:28+02:00
9 + 6x do kwadratu + x do potęgi czwartej
25a do kwadratu - 20ab + 4b do kwadratu
25 - 10x + x do kwadratu
36y do kwadratu - 36y + 9
1 - 9x do kwadratu
  • Użytkownik Zadane
2009-05-21T18:04:09+02:00
(3+x²)²=(3+x²)*(3+x²)=9+3x²+3x²+x4=9+6x²+x4

(5a-2b)²=(5a-2b)*(5a-2b)=25a²-10ab-10ab+4b²=25a²-20ab+4b²

(-6y-3)²=(-6y-3)*(-6y-3)=36y²+18y+18y+9=36y²+36y+9

(-3x+1)(1+3x)=-3x-9x+1+3x=-9x+1
2009-05-21T18:05:58+02:00
1.(3+x²)²=
9+4x=
4x=-9 /÷4
x=2,5

2.(5a-2b)²=
25a-4b=

3.(-5+x)²=
25+2x=
2x=-25/÷2
x=12,5


4.(-6y-3)²=
6y+9=
6y=-9/÷3
2y=-3/÷2
y=-1,5


5.(-3x+1)(1+3x)
-3x+1×1+3x
-3x+1×1+3x
-3x+3x×1+3x
-3x+3x+3x×1
3x×1
3x